The Construction of Motherhood Among Convict Female in Bandung, Indonesia - Vivi Patra Komala; Hani Yulindasari (SEA-CECCEP, 2022)
This study aims to explore the construct of a mother who is a convict. Imprisoned mothers have challenges that are different from mothers in general, such as limited carrying out of their motherly role in raising children, unclear mother's status both for herself and for her children, and agreed parenting identities. The number of female prisoners is increasing, but studies that focus on female prisoners in negotiating their maternal identity are very limited. In Indonesia, very few studies have been conducted on the upbringing of convict mothers, in contrast to western countries, where much research has been carried out on imprisoned mothers. This article uses post-structuralist feminist theory, it is hoped that problems will be more open by understanding this theory. The case study approach was the method used in this study, with the subject of two convict mothers who were in class 2A Women's Prison in Bandung. The research subjects were mothers who were separated from their children and mothers who brought their children to prison. Data collection was consucted through interviews. The results of this analysis found that the mother who is a convict tries to be the main caregiver for her child by negotiating her role through nurturing, caring, fulfilling needs and delaying her physical presence.